2004
DOI: 10.1021/jp030737l
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Surface Intermediates Formed by Selective Oxidation of Alcohols on Silica-Supported Molybdenum Oxide

Abstract: The behavior of surface species, formed from the adsorption of methanol and isobutyl alcohol (2-methyl-1-propanol) on MoO3/SiO2, was studied in an oxygen-containing atmosphere by in situ Fourier transform infrared spectroscopy (FTIR). At 250 °C, methanol adsorption resulted in the formation of surface methoxide species (CH3O−), whereas isobutyl alcohol adsorption resulted in surface isobutoxide species ((CH3)2CHCH2O−). Kinetic studies indicated that the rate-determining step for the alcohol oxidation was the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Furthermore, heterogeneous oxidations of alcohols over metal oxide catalysts have also been studied. The studied catalysts are the oxides of magnesium, [28][29][30] copper, 31 cerium, [32][33][34] titanium, [35][36][37][38][39] tungsten, 40 cobalt, 41 vanadium, 42 molybdenum, 43 niobium, 44,45 and zinc. 6,46,47 Recently semiconductor metal oxides nanoparticles have been widely used for heterogeneous oxidation of alcohols to the corresponding carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, heterogeneous oxidations of alcohols over metal oxide catalysts have also been studied. The studied catalysts are the oxides of magnesium, [28][29][30] copper, 31 cerium, [32][33][34] titanium, [35][36][37][38][39] tungsten, 40 cobalt, 41 vanadium, 42 molybdenum, 43 niobium, 44,45 and zinc. 6,46,47 Recently semiconductor metal oxides nanoparticles have been widely used for heterogeneous oxidation of alcohols to the corresponding carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[49,50,56,57] It is established that the initial step of the dissociative adsorption of alcohols on metal oxides is proton abstraction by a surface basic site. The surface of silica does not have such sites and hence cannot form 2-propoxide groups.…”
mentioning
confidence: 99%
“…Isotopic substitution studies in the 1980s already suggested that the OÀH bond breaking was an equilibrated process, while the CÀH bond breaking was the rate-limiting step for the reaction kinetics. [9][10][11] More recent work on the oxidation of methanol confirmed the existence of methoxy groups (ÀOCH 3 ) on the surface prior to oxidation. [12] These observations together with various kinetic studies, principally conducted through the combined efforts of research groups at Virginia Tech and Tokyo Institute of Technology, led to the proposal of a schematic reaction mechanism [Eqs.…”
Section: Introductionmentioning
confidence: 93%
“…Computational work has therefore always discussed both structures simultaneously giving a slight advantage to di-oxo structures. [9,16,18,20,21] When deduction of the reaction mechanism was the central goal, molybdenum supported on SiO 2 has received most attention. [15,18] The latest contribution of Gregoriades et al used a cluster model where the SiO 2 support was modeled as a polyhedral oligomeric silsequioxane (POSS).…”
Section: Introductionmentioning
confidence: 99%